2023
DOI: 10.3390/met14010007
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Behavior and Microstructure Evolution of an Extruded 6082 Aluminum Alloy Sheet at High Temperatures

Sawei Qiu,
Erli Xia,
Limei Liu
et al.

Abstract: The hot tensile behavior of an extruded 6082 alloy sheet at varying temperatures and strain rates was investigated by a Gleeble3500 thermal simulation testing machine. The optical microscope (OM), scanning electron microscope (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD) were applied to observe the microstructure evolution. It is found that the flow stress of the studied alloy declines with increasing deformation temperature. When deformed at high temperatures, the density of disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…For instance, when the samples were deformed relative to the conditions of 300 °C and 0.1 s −1 , the corresponding yield stress values were 137 MPa, 129 MPa, and 136 MPa for the 0°, 45°, and 90° samples, respectively. Similar trends of mechanical anisotropy have been observed in previous studies, and it was reported that fibrous grains and deformation texture are responsible for this form of regulation [ 31 , 32 ]. During plastic deformations, the grain boundary would hinder the movement of dislocations, and elongated grains result due to the different densities of the grain boundary along three loading directions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, when the samples were deformed relative to the conditions of 300 °C and 0.1 s −1 , the corresponding yield stress values were 137 MPa, 129 MPa, and 136 MPa for the 0°, 45°, and 90° samples, respectively. Similar trends of mechanical anisotropy have been observed in previous studies, and it was reported that fibrous grains and deformation texture are responsible for this form of regulation [ 31 , 32 ]. During plastic deformations, the grain boundary would hinder the movement of dislocations, and elongated grains result due to the different densities of the grain boundary along three loading directions.…”
Section: Resultssupporting
confidence: 88%
“…The experimental data imply that the specimens along the extrusion direction exhibit the maximum strength; meanwhile, the strength of the 90° specimen is the lowest. Qiu [ 31 ] investigated the response of a 6082 alloy processed via extrusion, and it was reported that the specimens along the extrusion direction have the highest stress level. This can be attributed to the elongated grains that formed during extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the alloy transitions into the plastic deformation stage, with an increase in stress corresponding to an increase in strain. The formation of a multitude of dislocation tangles and dislocation cells within the alloy leads to an increase in dislocation density [26], and the deformation process is predominantly governed by work hardening. Upon reaching the ultimate tensile strength, the alloy enters a stage where the stress decreases with increasing strain, during which softening behavior becomes more pronounced.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The brass texture formed during the cold rolling process accounts for the anisotropy of mechanical properties. Qiu et al [22] investigated the mechanical properties of an extruded 6082 aluminum alloy sheet. The results show that the elongated grain is able to trigger mechanical anisotropy.…”
Section: Introductionmentioning
confidence: 99%